Disturbed granite identification by integrating rock mass geophysical properties. (February 2021) - Lin, Daming; Yuan, Renmao; Lin, Xiaoling; Lin, Xuechun; Lou, Chonghua; Cai, Yanyan; Yu, Jin; Qiu, Renke; Su, Xingju; Wang, Hui
Abstract: Granite is exposed across 9% of China, and many major infrastructures are located in granitic areas because of the intact structure and high compressive strength of granite. Therefore, the identification of disturbed granite by integrating rock mass properties is important for construction safety. In this paper, the authors utilize data from 278 shallow boreholes and 12 geophysical exploration lines in South China and establish a 3-D geological-geophysical model. A quantitative relationship between the disturbed rock mass structure and rock core index ( RCI ) is then established. An empirical relationship between the electrical resistivity and the seismic velocity of the disturbed granite at the China Spallation Neutron Source (CSNS) site is also obtained. This research enhances the quantitative characterization of disturbed granite, especially disintegrated laminated granite, using rock mass geophysical parameters.